2019
DOI: 10.1016/j.jtho.2019.08.2035
|View full text |Cite
|
Sign up to set email alerts
|

EP1.01-62 The Safety Profile and Preliminary Efficacy of Ceritinib 450mg with Food in Chinese ALK/ROS-1 Positive NSCLC Patients

Abstract: complete response in 5% and progressive disease in 8%. Of the subjects undergoing chemotherapy (n¼102), 33 experienced grade 3 or 4 AE and 14 subjects had to discontinue chemotherapy before 4 cycles. ECOG PS improved to 0/1 in 22 (19.6%) subjects who underwent any form of treatment. The median survival of the study cohort was 250 days. On a multivariate analysis, the presence of brain metastases was associated with poor OS (HR [95% CI] 7.6 [1.4-41.6]) Conclusion: Most of the Elderly patients with NSCLC and poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The ASCEND-8 explored the administration pattern and dosage of ceritinib and found ceritinib 450 mg/d fed had similar pharmacokinetic profiles to 750 mg/d fed, but with significantly improved gastrointestinal events and better efficacy (9). Data from a real-world study (10) showed that ceritinib 450 mg/d fed demonstrated superior OR, disease control rate (DCR), and PFS in Chinese patients with brain metastases from ALK-positive NSCLC compared with a dose of 750 mg/d fasted, and therefore the approved dose for ceritinib in China is 450 mg/d.…”
Section: Dose Adjustment For Ceritinibmentioning
confidence: 99%
“…The ASCEND-8 explored the administration pattern and dosage of ceritinib and found ceritinib 450 mg/d fed had similar pharmacokinetic profiles to 750 mg/d fed, but with significantly improved gastrointestinal events and better efficacy (9). Data from a real-world study (10) showed that ceritinib 450 mg/d fed demonstrated superior OR, disease control rate (DCR), and PFS in Chinese patients with brain metastases from ALK-positive NSCLC compared with a dose of 750 mg/d fasted, and therefore the approved dose for ceritinib in China is 450 mg/d.…”
Section: Dose Adjustment For Ceritinibmentioning
confidence: 99%